Distance Estimation based on Color-Block: A Simple Big-O Analysis - Budi Rahmani; Hugo Aprilianto; Heru Ismanto; Hamdani Hamdani (International Journal of Electrical and Computer Engineering (IJECE), 2017)
This paper explains how the process of reading the data object detection results with a certain color. In this case the object is an orange tennis ball. We use a Pixy CMUcam5 connecting to the Arduino Nano with microcontroler ATmega328-based. Then through the USB port, data from Arduino nano re-read and displayed. It’s to ensure weather an orange object is detected or not. By this process it will be exactly known how many blocks object detected, including the X and Y coordinates of the object. Finally, it will be explained the complexity of the algorithms used in the process of reading the results of the detection orange object.